PERLINDUNGAN HUKUM TERHADAP PENGGUNA KARTU ATM TERTELAN DITINJAU DARI UU NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (STUDI PUTUSAN NO: 77/PEN/BPSK/MDN/2012) - Donny Mangiring Tua Siburian; Tan Kamello; Dedi Harianto; Utary Maharani Barus (Universitas Sumatera Utara, 2016)
ABSTRACT Transaction by using ATM (Automatic Teller Machine) has to be sure that his ATM card can withdraw money and secrecy of PIN (Personal Identification Number). A legal case in the ATM working system occurred that his ATM card was stuck in the machine and surprisingly he lost Rp. 76,800,000 from his accounts. The result of the research showed that protection for consumers in using ATM cards which are taken in ATM machines is regulated in Article 19, paragraph 1 of Law No. 8/1999 on Consumer Protection, Article 29, paragraph 5 of Law No. 10/1998 on Banking, the Regulation on Financial Service Authority No. 1/POJK.07/2013, and the Regulation of Bank Indonesia No. 16/1/PBI/2014 on Protection for Consumers as the Users of Financial System Service. It is recommended that regulation on legal protection for consumers whose ATM cards are taken in ATM machines, the uniformity of judge’s decision in BPSK verdict with the Court’s Ruling should also be established. Keywords: Legal Protection, ATM Card, Consumer Protection